Pharmacology practice and South Africa physiotherapists - part two needs analysis - M. Unger; R. Lochner (AOSIS, 2006)
A national survey of pharmaceutical practice by South African physiotherapists was conducted. In this second paper, the needs relating to administration, storage and prescription of medicines are discussed. Seventy percent of respondents reported a need to legally administer and 58% reported a need to store certain medicines. More than 60% of respondents were in favour of the expansion of the scope of physiotherapy practice to include prescription of a limited range of medications after training and within certain areas of specialization or clinical competence. It is recommended that a basic pharmacology module be part of the undergraduate curriculum with the option to expand or update knowledge and skills via CPD activities and through specialization and that legislation be revised to accommodate these suggestions.